Sarcopenic osteoarthritis: a new entity in geriatric medicine? - Veronese, Nicola; Punzi, Leonardo; Sieber, Cornel; Bauer, Jürgen M.; Reginster, Jean-Yves; Maggi, Stefania (European geriatric medicine, 2018)
Osteoarthritis, a disease characterized by cartilage degradation, abnormal subchondral bone remodeling and some grade of inflammation, and sarcopenia, a condition of low muscle mass associated with reduced strength and function, are prevalent disorders in older adults. In this review, we examine what is known about the relationship between osteoarthritis and sarcopenia, with particular focus on the older population. We also discuss how osteoarthritis and sarcopenia may interact and affect each other in clinical progression and the potential benefits from developing treatments that address such muscular-skeletal interaction.